Screening of jute varieties against jute apion (Apion corchori Marshall) and its management using chemical and botanical pesticides: Screening of jute varieties and its management (Journal of the Bangladesh Agricultural University, 2019)
The experiment was conducted in the field laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh on the screening of resistant variety against jute apion, Apion corchori (Marshall) and its management by using some chemical and botanical pesticides during April to August 2014. Eleven jute varieties were selected to conduct varietal preference and tested against jute apion in field condition. Among the eleven varieties, O-9897 showed the higher leaf infestation than others showing statistically similar result with O-72 and O-795. Mean percent of leaf infestation was 55.64 in O-9897 while 28.07 in BJRI Deshi pat-5, 24.89 in CVL-1, 22.11 in BJRI Deshi pat-7, 29.64 in CC-45, 24.08 in BJRI Deshi pat-8, 27.99 in D-154, 51.42 in O-795, 26.37 in BJRI Deshi pat-6, 55.53 in O-72 and 39.45 in CVE-3. The lowest leaf infestation was found in BJRI Deshi pat-7 (22.11%) which was statistically similar to BJRI Deshi pat-8 (24.08%). The same trend of results was observed in case of the number of knot plant-1 and the highest knot was recorded in O-795 followed by O-72. Data revealed that the variety O-9897 was highly susceptible to jute apion followed by O-72 and O-795 whereas BJRI Deshi pat -7 had the resistant potentiality against jute apion followed by BJRI Deshi pat-8 and CVL-1. The overall preference rank of the varieties based on their resistance against jute apion was in the following order: BJRI Deshi pat-7>BJRI Deshi pat-8>CVL-1 > BJRI Deshi pat-6> D-154>BJRI Deshi pat-5> CC-45>CVE-3>O-795>O-72>O-9897. In the management study, two synthetic insecticides viz., Limper 10EC, Diginol 60EC and two botanicals viz., Neem oil and Mahogany oil were evaluated. Considering different parameters, comparatively less leaf infestation percent, number of hole leaf-1 and number of knot plant-1 was found with Diginol 60EC treated plot followed by Limper 10EC treated plot. The highest infestation was found in the control plot followed by Mahogany oil applied plot.  The rank of the efficacy of the treatments was Diginol>Limper>Neem oil>Mahogany oil>control. It could be concluded that BJRI Deshi pat-7, BJRI Deshi pat-8 and CVL-1 was comparatively more resistant variety considering both leaf damage and number of knot plant-1 and local variety O-9897 followed by O-72 and O-795 was highly susceptible to Jute apion. This finding would be helpful to motivate the people to use botanical insecticides i.e., Neem oil for the management of jute apion in environmentally safe condition.J Bangladesh Agril Univ 17(3): 274–280, 2019